Graph Structures for Knowledge Representation and Reasoning 6th International Workshop, GKR 2020, Virtual Event, September 5, 2020, Revised Selected Papers - Cochez, Michael; Croitoru, Madalina; Marquis, Pierre; Rudolph, Sebastian (Lecture Notes in Computer Science; Lecture Notes in Artificial Intelligence, 2021)
This open access book constitutes the thoroughly refereed post-conference proceedings of the 6th International Workshop on Graph Structures for Knowledge Representation and Reasoning, GKR 2020, held virtually in September 2020, associated with ECAI 2020, the 24th European Conference on Artificial Intelligence. The 7 revised full papers presented together with 2 invited contributions were reviewed and selected from 9 submissions. The contributions address various issues for knowledge representation and reasoning and the common graph-theoretic background, which allows to bridge the gap between the different communities.